Coverage Path Planning Strategies for Low-Cost UAVs in Biological Control in Large Areas - Silva, Bruno Siqueira Da; Silva, Lian Lago; Cabreira, Taua Milech; Ferreira, Paulo R.; Brisolara, Lisane B. De; Jorge, Lucio A. C.; Matias, Nicholas R.; Machado, Ricardo A. O. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This study develops and validates coverage path planning strategies for low-cost UAVs in biological pest control in large agricultural areas. Two approaches were implemented in a web application: (i) decomposition of complete routes into subroutes using a back-and-forth pattern, and (ii) segmentation of areas through Voronoi diagrams for balanced partitions. Validation was carried out through real UAV flights under different payload configurations, with contributions from UAV and biological control experts. The results showed that the Subroutes algorithm covered 114.61 ha in 44 minutes and 48 seconds, while the Subareas algorithm reduced distance by 2.6 km (2.8%) and flight time by 1 minute and 51 seconds (4.1%), ensuring a more uniform workload distribution. These findings confirm the practical applicability of the proposed strategies and their potential to improve efficiency in UAV-based biological control operations.